Studies on Schismatoglottideae (Araceae) of Borneo XI: Ooia, a new genus, and a new generic delimitation for Piptospatha - Wong, Sin Yeng; Boyce, P.C (SpringerOpen Journal, 2010)
ABSTRACT A new genus, Ooia S.Y. Wong & P.C. Boyce is erected from Piptospatha sensu Bogner & Hay with two species: Ooia grabowskii (Engl.) S.Y. Wong & P.C. Boyce and Ooia kinabaluensis S.Y. Wong & P.C. Boyce. Ooia is unique in the Tribe Schismatoglottideae owing to the persistence of the entire spadix axis through to fruit maturation and dispersal, with the entire axis remaining fresh and the non-female flowers sloughing away. Species of Piptospatha sensu Wong & Boyce are here delimitated to include only the Elongata Group, which as defined by Bogner & Hay includes the type species, Piptospatha insignis N.E. Br., but which is known only from the type, itself of imprecise origin.